1996
DOI: 10.1063/1.363422
|View full text |Cite
|
Sign up to set email alerts
|

Hole transport properties of bulk zinc-blende and wurtzite phases of GaN based on an ensemble Monte Carlo calculation including a full zone band structure

Abstract: In this paper, we present calculations of the hole transport properties of bulk zinc-blende and wurtzite phase GaN at field strengths at which impact ionization does not occur significantly. The calculations are made using an ensemble Monte Carlo simulator, including the full details of the band structure and a numerically determined phonon scattering rate based on an empirical pseudopotential method. Band intersection points—including band crossings and band mixings—are treated by carefully evaluating the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…1) of the first BZ into fine tetrahedra, and store the band energies and the cell-periodic overlap parameters at the nodes of these tetrahedra. Even though the term # W j;m 0 ð W k 0 Þ is not confined to the IW, ZB and WZ point-group symmetry operations [8,9] can be applied to generate the images of the points in IW, and hence, the overall integration can essentially be performed exploiting the tetrahedra in IW. It needs to be mentioned that very fine division of the IW ($400,000 tetrahedra) is necessary to reduce the computational ripple, especially favoring the high-symmetry points where satellite valleys are present.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…1) of the first BZ into fine tetrahedra, and store the band energies and the cell-periodic overlap parameters at the nodes of these tetrahedra. Even though the term # W j;m 0 ð W k 0 Þ is not confined to the IW, ZB and WZ point-group symmetry operations [8,9] can be applied to generate the images of the points in IW, and hence, the overall integration can essentially be performed exploiting the tetrahedra in IW. It needs to be mentioned that very fine division of the IW ($400,000 tetrahedra) is necessary to reduce the computational ripple, especially favoring the high-symmetry points where satellite valleys are present.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…But they are based on simulation results of symmetric diode structures where the hole saturation velocity is assumed to be the same as the electron saturation velocity. This assumption is however incorrect in view of reports [4,5]. In report [4], Albrecht et al have used Monte Carlo simulations of electron transport based upon an analytical representation of the lowest conduction bands of bulk, wurtzite phase GaN to develop a set of transport parameters for devices with electron conduction in GaN.…”
Section: Introductionmentioning
confidence: 99%
“…In report [4], Albrecht et al have used Monte Carlo simulations of electron transport based upon an analytical representation of the lowest conduction bands of bulk, wurtzite phase GaN to develop a set of transport parameters for devices with electron conduction in GaN. On the other hand, in report [5], Oǧuzman et al have calculated the hole saturation velocity using an ensemble Monte Carlo simulator, including the full details of the band structure, and numerically determined phonon scattering rate based on empirical pseudopotential method. They found that the average hole energies are significantly lower than the corresponding electron energies believed to be due to the drastic difference in curvature between the uppermost valence bands and the lowest conduction band [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be an advantage since InGaN layers with high In content show a strong tendency for In segregation. The smaller effective mass and the higher mobility of free carriers in III-nitrides [4] and their larger saturation drift velocity is advantageous for high temperature electronic device applications. Finally, c-III-nitrides are mainly grown on semiconductor substrates with cubic crystal structure allowing easy cleavage of laser facets and possible future integration of III-nitrides with the advanced GaAs (Si-technology).…”
Section: Introductionmentioning
confidence: 99%